2021
DOI: 10.3390/molecules26247465
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Potential of Flower Extracts from Centaurea spp. Depends on Their Content of Phenolics, Flavonoids and Free Amino Acids

Abstract: Scientists intensely search for new sources of antioxidants, perceived as important health-promoting agents. Some species of the large genus Centaurea provide raw materials for the pharmaceutical and cosmetic industries, as well as produce edible flowers. This is the first study that determines the content of total polyphenols, flavonoids, reducing sugars, free amino acids and the antioxidant potential in the flower extracts of C. nigra L., C. orientalis L. and C. phrygia L. The total polyphenol and flavonoid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 43 publications
3
19
0
Order By: Relevance
“…The low values of IC50‐DPPH assay are associated with the high value of TPC and TFC contents indicating negative correlations. The positive correlations was explained by the high levels of TPC and TFC [21,22] . In our study, the strong Pearson's correlation c oefficient (r>0.7) showed that phenolic and flavonoid secondary metabolites are the major contribution to the antioxidant activity by DPPH method which are consistent with previous data [21] .…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The low values of IC50‐DPPH assay are associated with the high value of TPC and TFC contents indicating negative correlations. The positive correlations was explained by the high levels of TPC and TFC [21,22] . In our study, the strong Pearson's correlation c oefficient (r>0.7) showed that phenolic and flavonoid secondary metabolites are the major contribution to the antioxidant activity by DPPH method which are consistent with previous data [21] .…”
Section: Resultssupporting
confidence: 92%
“…[21,22] In our study, the strong Pearson's correlation coefficient (r > 0.7) showed that phenolic and flavonoid secondary metabolites are the major contribution to the antioxidant activity by DPPH method which are consistent with previous data. [21] Moreover, the number and position of hydroxy groups in phenolic compounds determine antioxidant activity, whereas the presence of glycoside moieties attenuates antioxidant activity. [23,24] In particular, the 3',4'-dihydroxy groups of the B-ring dominate their antioxidant activity.…”
Section: Molecular Dockingsupporting
confidence: 92%
“…In this study, only their total amino acid content was examined; however, interference from short‐chain polysaccharides and free amino acids is a possibility. According to Salachna, Pietrak, and Lopusiewicz (2021), reducing sugars and free amino acids possess antioxidant properties. Lacroix, Chen, Kitts, and Li‐Chan (2017) revealed that free amino acids, including Tyr, Leu, Pro, and Gln, exhibited modest ACE inhibition, etc.…”
Section: Resultsmentioning
confidence: 99%
“…According to Salachna, Pietrak, and Lopusiewicz (2021), reducing sugars and free amino acids possess antioxidant properties. phytochemicals, but it uses a lesser amount for peptides from plant proteins (Alashi et al, 2014b).…”
Section: Surface Hydrophobicity (H O ) Of Sph and Peptide Fractionsmentioning
confidence: 99%
“…Over the past several years, there has been growing interest in the plants of the genus Centaurea L. (Asteraceae), which is a genus with several hundred representatives and that is native to the Mediterranean basin but is practically widespread on most continents [ 17 , 18 ]. The plants are quite expansive and do not require special soil conditions [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%